Viral Culture in Hospitalized Congregate Care Patients With Prolonged SARS-CoV-2 Viral RNA Detection. (17th December 2021) - Arunachalam, Thilaka; Singh, Amit; Stellrecht, Kathleen; Elmendorf, Sarah; Barman, Tarani K; Robek, Michael; Metzger, Dennis W; Waxman, Michael
Abstract: Prolonged detection of SARS-CoV-2 viral RNA has been observed in hospitalized congregate care patients following resolution of clinical symptoms. It is unknown whether patients with persistent PCR positivity pose a risk for COVID-19 transmission. The purpose of this study was to examine the results of serial PCR testing, viral load, and viral culture in patients awaiting discharge prior to a negative PCR test. We sampled 14 patients who were admitted from skilled nursing and/or rehabilitation facilities to a large academic medical center, had clinical signs and symptoms of COVID-19, and had multiple PCR-positive tests separated by at least 14 days. PCR-positive nasopharyngeal swabs were obtained from each patient for viral load quantification and viral culture. The mean age of patients was 72.5 years (55 – 92), with a mean peak SOFA score of 5.6 (1 – 11). Patients were hospitalized for a mean of 37.0 days (25 – 60). RNA was detected by PCR for a mean of 32.9 days (19 – 47). Mean viral load for the first PCR-positive nasopharyngeal swab collected at our hospital was 5.81 genomic copies/mL (2.12 – 9.72). Viral load decreased significantly with days from clinical symptom onset (R = -0.69, 95% CI, -0.80 – -0.55). Four out of 28 samples grew active virus via culture, with no active virus isolates after 2 days of symptom onset. Our viral culture data suggests that persistent PCR positivity may not correlate with infectivity, which has important implications for COVID-19 infection control precautions among older congregate care patients.